2007
DOI: 10.1007/s11010-007-9498-2
|View full text |Cite
|
Sign up to set email alerts
|

Decreased dopamine D2 receptor function in cerebral cortex and brain stem: their role in hepatic ALDH regulation in ethanol treated rats

Abstract: Ethanol exerts numerous pharmacological effects through its interaction with various neurotransmitters. The dopaminergic pathway is associated with cognitive, endocrine, and motor functions, and reinforcement of addictive substances or behaviours. Aldehyde dehydrogenase (ALDH) is a vital enzyme involved with alcohol metabolism and detoxification. In the present study, we investigated the role of cerebral cortex and brain stem dopamine D(2) receptors in the functional regulation on ALDH enzyme activity, in etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In our logistic regression analysis tobacco smoke and alcohol use were significantly associated with aberrant methylation of RARβ 2, SPARC , LINE 1 and DRD 2 loci in AA patients with PCa suggesting that methylation of these genes could be associated with increased risk of PCa in patients who smoke tobacco and or consume alcohol. There are numerous reports to show that alcohol action is directly associated with neurotransmitters such as dopamine and serotonin and its receptors [ 48 , 49 ]. Our present observation of aberrant methylation in the DRD 2 gene and alcohol and/or tobacco use in blood samples from AA patients with PCa indicates that the status of DRD 2 methylation is correlated with lifestyle factors such as alcohol consumption and tobacco smoke in addition to serum vitamin D (discussed above) in AA PCa patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our logistic regression analysis tobacco smoke and alcohol use were significantly associated with aberrant methylation of RARβ 2, SPARC , LINE 1 and DRD 2 loci in AA patients with PCa suggesting that methylation of these genes could be associated with increased risk of PCa in patients who smoke tobacco and or consume alcohol. There are numerous reports to show that alcohol action is directly associated with neurotransmitters such as dopamine and serotonin and its receptors [ 48 , 49 ]. Our present observation of aberrant methylation in the DRD 2 gene and alcohol and/or tobacco use in blood samples from AA patients with PCa indicates that the status of DRD 2 methylation is correlated with lifestyle factors such as alcohol consumption and tobacco smoke in addition to serum vitamin D (discussed above) in AA PCa patients.…”
Section: Discussionmentioning
confidence: 99%
“…It alters their membranes as well as their ion channels, enzymes, N ‐methyl‐ d ‐aspartate (NMDA), and gamma‐aminobutyric acid (GABA) receptors. There are numerous reports showed EtOH action is directly associated with neurotransmitters such as dopamine, serotonin, GABA, NMDA, and its receptors (Benjamin et al., ; Fernando, ; George et al., , , ; McClintick et al., ; Spencer et al., ). Primary mechanism by which EtOH affects the brain is through regulation of neurotransmitters and ligands, voltage‐gated channels that are essential for neuronal excitability and synaptic function (Hoffman, ).…”
Section: Alcohol and Impaired Brain Function In Association Of Nmda Amentioning
confidence: 99%
“…The functional regulation of the central GABA and 5-HT 2 receptors during liver regeneration (Sudha and Paulose 1998;Biju et al 2001Biju et al , 2002Pyroja et al 2007), decreased alpha1-adrenergic receptor binding in the cerebral cortex and brain stem during pancreatic regeneration (Ani et al 2006) and decreased dopamine D 2 receptor binding in the hypothalamus and brain stem of streptozotocindiabetic rats (Shankar et al 2007) were reported form our lab. The cerebral cortex and brainstem DA D 2 functional regulation contributed to the central nervous system manifestations in ethanol-treated rats is also reported (George et al 2007). Ethanol exposure alters the function of neurotransmitter receptors.…”
Section: Discussionmentioning
confidence: 95%